Fatigue life analysis of hydropower pipelines using the analytical model of stress concentration in welded joints with angular distortions and considering the influence of water hammer damping. (February 2021) - Adamkowski, Adam; Lewandowski, Mariusz; Lewandowski, Stanisław
Abstract: The paper describes the procedure for assessment of the fatigue life of steel penstocks in hydropower plants based on the theory of crack propagation. The authors pay particular attention to several issues that have a substantial impact on the fatigue strength evaluation of the analyzed structures, such as stresses distribution in the material of penstock shells (walls), variability of their amplitude and frequency, and forecast of future operation of the considered hydropower plants. The proposed procedure in combination with other relatively simple methods e.g. for determining the stress concentration factor ( SCF ) in the penstock shells with angular distortions basing on analytical model, gives the possibility of its easy use in engineering practice for comprehensive estimation of the fatigue life characteristic of such structures. The authors, basing on tests carried out on real objects, used the developed procedure for assessment of the fatigue life to determine the impact of the uncommon method of damping the water-hammer accompanying the transient states of the hydropower units on increasing the fatigue strength of the steel penstock structures. Results obtained may contribute to the extension of good engineering practices in the field of operation methods of hydroelectric power plants equipped with steel penstocks and procedures for the safe maintenance of this type of structures. Highlights: Procedure for fatigue life assessment of thin walled steel pipelines was developed. Linear theory of crack propagation and damage accumulation hypothesis as well as the rainflow counting algorithm was used. Universal formula for the stress coefficient factor in angular distortions of welded pipeline shells was developed. Original method of damping the waterhammer in the pumped-storage power plant supplied by steel penstocks was investigated. Usefulness of this method was assessed using the procedure developed for fatigue life analysis of the penstock.